The Effect of Agricultural Technology on Shifts in Cultural Values in Rural Communities - Rizki Kurniawan; Andayu Farah Devani; Hasri Maghfiruotin Nisa (Nusantara Science and Technology Proceedings)
Social life tends to be fickle. Technological development is often one of the factors causing changes that occur in people's lives. The Wiwitan tradition is a form of celebration or a form of gratitude from farmers in the village of Sumberagung, District of Perak, Jombang, East Java for the harvest. Wiwitan is a tradition the origin from Java to start the rice harvest process as a form of gratitude towards Dewi Sri or Dewi Padi. This tradition also aims to establish friendship between the surrounding communities. The existence of technological developments in agriculture that namely the Combine Harvester machine as a modern rice harvesting machine is considered to cause the number of rice harvesters in the village to decrease. Wiwitan is no longer carried out on a large scale of activities but only focused on small group of farmers. This study aims to determine how the effect of technology in shifting the values of mutual cooperation and togetherness in rural communities, especially people who work as farmers in Sumberagung Village, District of Perak, Jombang, East Java. Researchers used a qualitative description study by taking data through in-depth interviews and literature studies. The informants of this research are farmers and community leaders in the village. The results of this study explain how agricultural technology provides changes to the lives of rural communities.